Patient and healthcare professional perceptions of colostomy-related problems and their impact on quality of life following rectal cancer surgery. Issue 5 (7th May 2018) - Elfeki, H; Thyø, A; Nepogodiev, D; Pinkney, T D; White, M; Laurberg, S; Christensen, P; ,
Abstract: Background: The perception of colostomy-related problems and their impact on health-related quality of life (QoL) may differ between patients and healthcare professionals. The aim of this study was to investigate this using the Colostomy Impact Score (CIS) tool. Methods: Healthcare professionals including consultant colorectal surgeons, stoma nurses, ward nurses, trainees and medical students were recruited. An online survey was designed. From the 17 items used to develop the CIS, participants chose the seven factors they thought to confer the strongest negative impact on the QoL of patients with a colostomy. They were then asked to rank the 12 responses made by patients to the final seven factors contained in the CIS. Results were compared with the original patient rankings at the time of development of the CIS. Results: A total of 156 healthcare professionals (50·4 per cent of the pooled professionals) from 17 countries completed the survey. Of the original seven items in the CIS, six were above the threshold for random selection. Ranking the responses, a poor match between participants and the original score was detected for 49·7 per cent of the professionals. The most under-rated item originally present in the CIS was stool consistency, reported by 47 of the 156 professionals (30·1 per cent), whereas frequency of changing the stoma bag was the item not included in the CIS that was chosen most often by professionals (124, 79·5 per cent). Significant differences were not observed between different groups of professionals. Conclusion: The perspective of colostomy-related problems differs between patients with a colostomy and healthcare professionals. Graphical Abstract: There is a substantial discrepancy in perspectives between colostomy patients and healthcare professionals. Further awareness and a better understanding of the mechanisms by which a colostomy affects a patient's quality of life (QoL) is required to improve both clinical practice and future research efforts. Professionals have a different look at colostomy-related problems